Examining Deep-Level Diversity in Top Management Teams: Team Power Distribution and Team Cognitive Diversity - Iglesias, Ana Elisa Arouca (Journal of Applied Business and Economics, 2023)
This empirical study draws on research in sociology and cognition to examine the relationship between two deep-level diversity constructs: team power distribution and team cognitive diversity. Team power distribution reflects the extent to which power is distributed among team members evenly (team power equality) or unevenly (team power inequality). Team cognitive diversity reflects the extent to which strategic beliefs are held in common by the whole team (strategic consensus) or subgroups within the team (strategic dissent). Rather than using demographic measures as proxies for team cognition, this study employs a cognitive elicitation method to capture the mental models of 342 top managers from 49 US hospitals. I find that distinct power patterns are associated with distinct patterns of cognitive diversity, which suggests that the extent to which power is distributed within the team may affect the extent of strategic consensus and dissent within top management teams (TMTs). These findings contribute to the growing literature on group processes and managerial cognition.